A Case of a Giant Intracranial Arachnoid Cyst Mimicking Cerebrovascular Accident in a Sickle Cell Disease Patient (Nigerian Journal of Health Sciences, 2023)
Stroke or cerebrovascular accident (CVA) is a common vascular neurological condition. Many cranial lesions produce stroke-like features and may be mistaken for stroke. The aim of case report was created the awareness of the possibility of rare conditions such as this benign giant arachnoid cyst presenting with neurological symptoms mimicking CVA. We present a case of a 53-year-old female sickle cell disease patient who had features highly suggestive of CVA and had been previously managed as such before presenting to us. The patient had cranial magnetic resonance imaging as part of her neurologic evaluation, and this revealed a giant intracranial arachnoid cyst. She subsequently had craniotomy for excision of the mass lesion following which she had an uneventful postoperative recovery and sustained neurological improvement. This case illustrates similarities in the presentation of CVAs and intracranial arachnoid cysts. The value of brain imaging in the evaluation of patients with clinical features of CVA is also shown. This imaging was essential in arriving at an accurate differential diagnoses of CVAs and thus direct appropriate treatment.